Smart cities : a panacea for sustainable development - Oke, Ayodeji Emmanuel; Stephen, Seyi Segun; Aigbavboa, Clinton Ohis; Ogunsemi, Deji Rufus; Aje, Isaac Olaniyi (Emerald points., 2022)
Professionals in the construction industry must respond quickly to meet the increasing pressures of heightened urban migration, and provide sustainable alternatives to resource scarcity in established cities - Smart Cities offers solutions to the demands of rising urban populations. The smartness of a city stems from the relationship between construction stakeholders and the citizens, with the shared goal to improve all standards and support social, physical, and economic growth. Surplus and reusable are key terminologies when striving towards sustainable development. Smart Cities aims to provide necessary information on the adoption of smart cities concepts towards achieving sustainable development, with a view to ensuring socially cohesive and resilient urban districts for both the current and future generations.